Replacement of Fish Oil With Groundnut Oil for Developing Sustainable Feeds for Labeo rohita Fingerling - Siddiqua, Kazi Sabnam; Khan, Mukhtar A. (Frontiers in Sustainable Food Systems, 2022)
Groundnut oil (GO) is one of the most widely available vegetable oils (VOs) from India and throughout the world, with the global production of 6.12 million metric tons in the year 2020-21. GO contains phytochemicals and antioxidants with a longer shelf life. Because of these benefits, GO can produce durable, low-cost, sustainable aquaculture feeds. In order to evaluate the nutritional efficacy and possibility of replacing fish oil (FO) with GO, this experiment was carried out to test the effects of partial or total substitution of dietary FO by GO on growth performance, carcass composition, antioxidant capacity, lysozyme activity, muscle fatty acid composition and fillet nutritional quality in Labeo rohita fingerling. Induced bred healthy rohu fingerling (4.84 ± 0.13 g) were fed six isonitrogenous (400 g kg-1) and isolipidic (97 g kg-1) casein and gelatin containing purified diets wherein the FO was gradually replaced by 0, 20, 40, 60, 80 and 100% GO. Fishes were stocked randomly in triplicate groups of 30 fish per tank and fed at 08:00, 12:00, and 16:00 hr to apparent satiety for 8 weeks. The results showed that FO replacement with GO did not affect the growth but decreased eicosapentaenoic (EPA), docosahexaenoic acid (DHA) levels, and n-3/n-6 ratio in the muscle of rohu fingerling. Antioxidant capacity and lysozyme activity improved up to 60% replacement of FO with GO in diet and then declined (P > 0.05) upon further inclusion of GO in diets. Although the atherogenicity, thrombogenicity indices and hypocholesterolaemic/hypercholesterolaemic (H/H) ratio did not change significantly among all the muscle samples, the highest fillet lipid quality (FLQ) value was found in fish receiving a 100% FO diet. Further inclusion of dietary GO decreased fillet H/H ratio and FLQ value. In summary, replacing FO with GO at a higher level had negative consequences on the fillet nutritional quality of rohu fingerling. Therefore, FO can be replaced by GO in formulated feeds to a level of 60% without hampering the growth, antioxidant capacity and lysozyme activity and to avoid degrading the nutritional quality of fish fillet.